Does perceived stress mediate a potential relationship between physical activity and sleep quality among adolescents? - Irja Gröndal 1996- (2022)
Healthy habits established during adolescence appear to persist throughout adulthood. However, decreased physical activity (PA), poor sleep quality (SQ) and increased stress seem to be the hallmarks of the adolescent years. Studies have reported associations between these health-related behaviours, but how they interrelate is less known. Thus, the current study aimed to examine the relationship between these behaviours and investigate whether stress mediates the association between PA and SQ. This cross-sectional study included 150 first-year upper-secondary students in Reykjavik, Iceland. A questionnaire was used to assess participants’ PA, SQ (Pittsburgh Sleep Quality Index: PSQI) and stress (Depression, Anxiety, Stress Scale: DASS-21). Pearson correlations were conducted to determine the relationships between the variables. The results showed a significant association between stress and SQ but not between the other variables. Mediation analysis was used to test whether stress mediated the relationship between PA and SQ. Results revealed that stress did not mediate the relationship between PA and SQ. These findings suggest that stress management could improve adolescents’ SQ, but further research on this association is needed. Future research could consider investigating the effects of specific stress management techniques, such as PA, on adolescents’ SQ. Keywords: physical activity, sleep quality, stress, adolescence Heilbrigðar venjur sem myndast á unglingsárunum virðast fylgja einstaklingum inn í fullorðinsárin. Hins vegar virðist minni hreyfing, léleg svefngæði og aukin streita einkenna unglingsárin. Rannsóknir hafa greint frá tengslum milli þessara heilsutengdu venja, en hvernig þær tengjast innbyrðis hefur verið minna rannsakað. Markmið þessarar rannsóknar var því að kanna tengsl milli þessara venja og athuga hvort streita hafi miðlunaráhrif á tengsl hreyfingar og svefngæða hjá ungmennum. Þátttakendur í þessari þversniðsrannsókn voru 150 nemendur á fyrsta ári í framhaldsskóla í Reykjavík. ...